Response of onion plant (Allium cepa) to the addition of Bio-humic fertilizer and planting date on the productivity characteristics of bulb yield - Nasser J. Kashash; Laila T. Fadala; Basim K. Hassan (University of Thi-Qar Journal of agricultural research, 2024)
The experiment was carried out in Dhi Qar Governorate - Nasiriyah City - Al-Mustafawiyah area, for the agricultural season 2023/2024 in one of the open plastic houses affiliated with the Agricultural Research Station for the fields of the Department of Horticulture and Landscape Engineering - College of Agriculture and Marshes, University of Dhi Qar. In a sandy loam soil to studying Response of onion plant (Allium cepa) to the addition of Bio-humic fertilizer and planting date on the productivity characteristics of bulb yield. The experiment was carried out using a Randomized Complete Block Design (R.C.B.D). The experiment included four treatments for adding biohumic fertilizer - control treatment (spraying with distilled water only), concentration (3) kg. ha-1, concentration (6) kg. ha-1, concentration (9) kg. ha-1 and three treatments for planting dates - the first date 10.20.2023, 01.11.2023 and the third date 10.11.2023. The addition of biofertilizer at a concentration of 6 kg.ha-1 was superior Giving the highest onion diameter, onion weight, onion neck diameter and onion length, the total yield of the plant from the bulbs, significantly at a concentration of 6 kg.ha-1, in giving the largest onion diameter, which reached (7.967 cm) and (94.06 g) and 35.37 mm) reached 11.126 cm 18.807 tons ha, respectively, and the first date (10/20) was superior to giving the highest onion diameter, onion weight, onion neck diameter and onion length, the total yield of the plant from the bulbs reached (8.158 cm) 90.15 g) 30.76 mm 18.027 tons ha-1